The Influence of Quality of Human Resources, Wages, Labor Force on Job Opportunities in Banten Province - Ardiyanti, Anita; Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The aim of this research is to analyze quality of human resources, wages, population growth, and the labor force on employment opportunities in West Nusa Tenggara Province either partially or simultaneously. The research method uses a quantitative approach using time series secondary data with a period of 8 years, namely 2015-2022. The dependent research variable is Job Opportunity (Y) Independent variables namely, quality of human resources (X1), wages (X2), and labor force (X3). Data collection through a documentation study, the collected data were analyzed with multiple linear regression, then tested using the T-test, namely that workforce (X3) have no significant effect on Job Opportunities. Meanwhile, the variables Quality of Human Resources (X2) and Wages (X3) have a significant effect on Job Opportunities in Banten Province. while the F-test simultaneously shows that Quality of Human Resources, Wages, the labor force have a significant effect on Employment Opportunities in the Province of Banten. This conclusion has shown that employment opportunities, and the impact of i fluctuations are caused by a slowdown in the export sector, and also a slowdown in investment growth. Labor force growth does not affect employment opportunities. Because the increase in population is not balanced with infrastructure, and investment.